The Health Care Revolution : From Medical Monopoly to Market Competition. - Ameringer, Carl F. (California/ Milbank Books on Health & the Public., 2004)
America's market-based health care system is the product of a revolution that overthrew the medical monopoly in the late 1970s. This book tells how this revolution came into being when the US Supreme Court and Congress prompted the antitrust agencies of the federal government to change the rules of the health care system.